PENGUKURAN KINERJA MANAJEMEN META DALAM ORGANISASI MAYA MENGGUNAKAN LOGIKA KABUR - Bambang Suratno (Faculty of Industrial Technology Universitas Islam Indonesia, 2015)
Competitive advantage is the keyword for Small Medium Enterprise (SME) to survive. One of the effort that could be conducted by the SMEs is doing temporary cooperation. The SMEs would arrange work contract hence all of the SMEs could work in same corridor. Development of Information Technology (IT) will support such cooperation and the SMEs would form a Virtual Organisation (VO). In VO, the management is called as meta-management, that contained several actions to coordinate all of the SMEs in the VO. Technically, the meta-management contained basic activities including analysing and tracing prerequisites, allocating requirements fulfilment and adjusting optimum criteria for every UKM. In term of management control, it requires a tool to measure success of the meta-management so that strategic actions could be arranged for future improvement. This paper presents the use of Fuzzy Logic (FL) to measure success of a meta- management. The success itself is measured based on the three aspects explained above, and the proposed FL is used to model uncertainties in every aspect. A numerical example from previous research is taken to show how the proposed method works.